Cerebrovascular disease: CeAD and migraine : an association built on shifting sands - Grond-Ginsbach, Caspar; Kloss, Manja (Nature reviews. Neurology, 2017)
A growing body of evidence indicates that people with migraine have an increased risk of cervical artery dissection (CeAD). A new study in young patients with ischaemic stroke has identified a specific link between CeAD and migraine without aura.
Gesehen am 01.06.2018